2007
DOI: 10.1021/om061183m
|View full text |Cite
|
Sign up to set email alerts
|

Carbon−Oxygen and Carbon−Hydrogen Bond Cleavage Reactions of ortho-Substituted Phenols by Ruthenium(II) Complexes

Abstract: Treatment of Ru(η 4 -1,5-COD)(η 6 -1,3,5-COT) (1) (COD ) cyclooctadiene (C 8 H 12 )) with a monosubstituted phenol HOC 6 H 4 (R 1 -2) (R 1 ) OMe, CHO, CO 2 Me) in the presence of PMe 3 gives corresponding oxaruthenacycle complexes formulated as cis-On the basis of the reaction profiles monitored by NMR spectroscopy, a mechanism involving a cationic η 5 -cyclooctadienylruthenium(II) intermediate, [Ru(η 5 -C 8 H 11 )(PMe 3 ) 3 ][OAr] (11), followed by the carbon-heteroatom bond cleavage is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Transition-metal atom, ion, metal clusters as well as metallic oxides that could convert this gas into valuable chemicals have attracted much attention. In particular, metal ions, serving as a prototypical model of heterogeneous catalysis, with CO 2 have been studied extensively. Bohme and co-workers reported detailed results of the transition-metal ions react with CO 2 in the gas-phase. They found that only nine transition-metal ions can get O from CO 2 at room temperature, with lots of heat released, but others can only form M + (CO 2 ) complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Transition-metal atom, ion, metal clusters as well as metallic oxides that could convert this gas into valuable chemicals have attracted much attention. In particular, metal ions, serving as a prototypical model of heterogeneous catalysis, with CO 2 have been studied extensively. Bohme and co-workers reported detailed results of the transition-metal ions react with CO 2 in the gas-phase. They found that only nine transition-metal ions can get O from CO 2 at room temperature, with lots of heat released, but others can only form M + (CO 2 ) complexes.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained FTIR spectra of Ru-1 and Ru-2 in KBr pellets are shown in Figures S6 and S7 . In the FTIR spectrum of Ru-1 and Ru-2 , the absorptions due to the stretching vibrations of the carboxylato unit have been recognized at 1597 and 1350 cm −1 [ 35 , 36 ]. The band at 702 cm −1 is attributed to the Ru–O stretch of Ru-1 .…”
Section: Resultsmentioning
confidence: 99%
“…One of the key factors in such bond activation processes is how to bring a C−H bond in proximity to the ruthenium center . In fact, the C−H bond cleavage reactions of phosphates, isonitrile, carbonyls, alcohols, phenols, carboxylic acids, amines, and pyridines are documented and these reactions are considered to involve prior coordination (or covalent bond formation) step before the C−H bond cleavage reactions. In addition, the C−H bond cleavage reactions by cleaving the covalent metal−chalcogen bond such as σ bond metathesis and electrophilic substitution currently attract a great deal of interest as new potential pathways for molecular transformation. , …”
Section: Introductionmentioning
confidence: 99%